Título Padrão - Lage, Sandra Regina Moitinho (Informação em Pauta, 2025)
In times when researching the theme "Health" becomes recurrent and fundamental, this thesis brings as a question whether the content of cordel leaflets of circumstance, produced by the poet Manoel Monteiro, represents reliable information, when produced themes relevant to health. To answer the question, we aimed to analyze how issues related to health are represented in cordel leaflets produced by the poet Manoel Monteiro. Specifically, the thesis had as a requirement to characterize the relevance of the area of Information Science, in particular the Thematic Representation of Information; to verify the circumstantial and informative character of the cordel leaflets analyzed and to compare the health themes presented in Manoel Monteiro's cordels, based on validated scientific documents. This is a bibliographic, documental, descriptive, and qualitative study, in which intentional sampling and the Integrative Bibliographic Review were employed, whose purpose is to gather, build, and synthesize results that are related to the theme as a contribution to the researched subjects. Thus, after access to 163 (one hundred and sixty-three) leaflets of the poet, we chose to analyze ten (10) leaflets, characterized as cordéis of circumstance, since they assume the role of informing themes pertinent to public health. Applying Lexical Field Theory, it was possible to identify the informational content of the leaflets, namely: Mental Health; Aging; Sexually Transmitted Infections; Social Vulnerability; Healthy Eating; Climate Change; Smoking and Harmful Substances; Diabetes Mellitus; Gender Violence; and Youth Violence. It is concluded that the leaflets are important informational resources since as one of the main validation criteria, they are based on scientifically approved documents. It is noteworthy that studies in Information Science, encompassing the Thematic Representation offer users, in the search for the desired information, possibilities of access and retrieval of documentary content. Thus, the interest and competence of Information Science is highlighted, in the dialogue and intersection with other Sciences, reinforcing its interdisciplinary character when collaborating with other scientific knowledge and, thus, allowing to broaden perspectives with a view to the process of democratization and socialization of information.